2018
DOI: 10.5194/acp-2018-273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical composition of isoprene SOA under acidic and non-acidic conditions: Effect of relative humidity

Abstract: Abstract. The effect of acidity and relative humidity on bulk isoprene aerosol parameters has been investigated in several studies, however few measurements have been conducted on individual aerosol compounds. While the focus of this study 10 has been the examination of the effect of acidity and RH on secondary organic aerosol (SOA) chemical composition from isoprene photooxidation in the presence of NOx, a detailed characterization of SOA at the molecular level have been also conducted. Experiments were condu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, some studies found that the production of isoprene-derived organosulfates was decreased at high RH levels possibly due to the dilution of particle acidity and sulfate nucleophiles. 55,56 Given that biogenic isoprene emissions are reported to be generally low in Xi'an and the surrounding areas during wintertime, 57−59 the acid-catalyzed uptake of isoprene-derived epoxydiols might be not quite prevalent or at least not a dominant pathway for the OrgS formation in this area.…”
Section: Sources and Formationmentioning
confidence: 99%
“…Nevertheless, some studies found that the production of isoprene-derived organosulfates was decreased at high RH levels possibly due to the dilution of particle acidity and sulfate nucleophiles. 55,56 Given that biogenic isoprene emissions are reported to be generally low in Xi'an and the surrounding areas during wintertime, 57−59 the acid-catalyzed uptake of isoprene-derived epoxydiols might be not quite prevalent or at least not a dominant pathway for the OrgS formation in this area.…”
Section: Sources and Formationmentioning
confidence: 99%